Natural Killer Cells from the Subcutaneous Adipose Tissue Underexpress the NKp30 and NKp44 in Obese Persons and Are Less Active against Major Histocompatibility Complex Class I Non-Expressing Neoplastic Cells - Shoae-Hassani, Alireza; Behfar, Maryam; Mortazavi-Tabatabaei, Seyed Abdolreza; Ai, Jafar; Mohseni, Rashin; Hamidieh, Amir Ali (Frontiers in Immunology, 2017)
There are many types of leukocytes reside in subcutaneous adipose tissue, and among them, natural killer cells (NKs) comprise a major part. We show that the NK cells that reside in the subcutaneous adipose tissue (ADNKs) of the abdominal region found with phenotypic differences from the NKs circulating in the peripheral blood (PBNKs). In this survey flow cytometry phenotyping was used to study the differences between the natural cytotoxicity receptor expression on ADNKs and PBNKs of both obese and lean persons. Also, their cytotoxicity and cytokine production patterns were evaluated. The activation experiments on isolated and expanded NKs with IL-2, IL-15, and IL-21 cytokines revealed the main population of the CD56dim within the total ADNKs of obese persons has an under-expression of NKp30 and NKp44 despite the unchanged levels of NKG2D. The data suggest the suppressive condition of the adipose tissue niche on the NKs response against sensitive MHC-I non-expressing neoplastic cells. As the NKs are the first line of the body’s defense versus tumor formation, this change may lead to the development of transformed cells into the tumors.